Multicyclic vibration control of a helicopter rotor with active twist actuation - Kim, D.H.; Hong, S.; Jung, S.N. (My University, 2021)
The vibration control performance of a Mach scaled Bo-105 rotor is evaluated using active twist multicyclic control. The simulation data for the baseline flight condition are generated using CAMRAD II. A linear, quasistatic, frequency domain model with up to six multicyclic higher harmonic control inputs and twelve harmonic response outputs of nonrotating hub loads are identified offline by the least squared error estimate. The optimal control input for minimizing the quadratic performance function along with the output response to the optimal control are calculated. The vibration reduction performances with the obtained optimal control input are calculated. The single harmonic control results show close agreement with the low vibration conditions by the amplitude and phase sweep method. When multicyclic control is applied, vibration reduction performance is improved compared to single harmonic control, and nonrotating hub vibration is reduced by up to 64%. A coupling of MATLAB and CAMRAD II is introduced to evaluate closed-loop multicyclic control systems. The coupled closed-loop analysis result shows good agreement with the simulation result using identified linear system model. The closed-loop control using the gradient descent algorithm shows very good vibration reduction performance and the reduced vibration level converges to the optimal solution.